The Prince of Biscari and the Prince of Torremuzza, «i due Dioscuri della passione antiquaria settecentesca» (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2016)
Ignazio Vincenzo Paternò Castello di Biscari (1719-1786) and Gabriele Lancillotto Castelli di Torremuzza (1727-1792) are certainly among the most important representatives of 18th century Sicilian culture. Well known all over Europe, hosts for the learned travellers that, always more numerous, visited the Island, corresponding with Italian and European scholars, the two princes are famous, in particular, for their incessant collecting activity, for their engagement in the safeguard of ancient monuments and, especially for Torremuzza, for their scientific publications regarding sometime – chiefly for Biscari – objects of their collections. In this study, it is integrally published, for the first time, their reciprocal correspondence that, although only partially preserved, offers an interesting picture of the great themes of 18th century antiquarianism: collecting, archaeological investigations, learned studies, not disregarding the “social” and engaged dimension that, according the more progressive mentality of the time, should be typical of the intellectual, especially if an aristocratic one.
Keywords: Sicily; 18th century; antiquarianism; safeguard of ancient monuments; collecting